Evidence of increased mussel abundance related to the Pacific marine heatwave and sea star wasting. (13th July 2022) - Traiger, Sarah B.; Bodkin, James L.; Coletti, Heather A.; Ballachey, Brenda; Dean, Thomas; Esler, Daniel; Iken, Katrin; Konar, Brenda; Lindeberg, Mandy R.; Monson, Daniel; Robinson, Brian; Suryan, Robert M.; et al.
Abstract: Mussels occupy a key middle trophic position in nearshore food webs linking primary producers to predators. Climate‐related environmental changes may synergistically combine with changes in predator abundance to affect intertidal ecosystems. We examined the influence of two major events on mussel ( Mytilus trossulus ) abundance in the northern Gulf of Alaska: the recent Pacific marine heatwave (PMH, 2014–2016) and an outbreak of sea star wasting (SSW). We investigated how mussel abundance changed since the onset of SSW and whether the density of predatory sea stars or PMH‐related temperature metrics explain variation in mussel abundance. Sea stars and mussels were surveyed since 2005 approximately annually in four regions of the northern Gulf of Alaska: Katmai (KATM), Kachemak Bay (KBAY), Kenai Fjords (KEFJ) and western Prince William Sound (WPWS). Mussel percent cover in the mid‐intertidal increased 1–3 years after declines in sea stars at all regions and in the low‐intertidal at KATM, KBAY, and KEFJ, but not at WPWS. After the onset of SSW, large (≥20 mm length) mussel density and mussel bed width increased at KATM but not the other regions. Total mussel densities, including recruits, did not differ before and after the onset of SSW. The total number of sea stars significantly explained variation in mussel metrics, but the proportions of the three sea star species examined did not. We did not find strong evidence for direct effects of temperature on mussels. The effects of the PMH and the SSW outbreak appear to have combined, with increased temperatures indirectly benefiting mussels in concert with relaxed top‐down pressure from sea stars, allowing for increased mussel abundance. Changing mussel abundance may affect intertidal local productivity and the abundance or performance of other nearshore consumers of mussels.